Mozart's Tempo-System A Handbook for Practice and Theory - Breidenstein, Helmut (Tectum Wissenschaftsverlag, 2019)
A reference book for the musician's practical work of interpretation, this volume, after a general presentation of 18th century principles for determining a tempo, offers a compendium of all Mozart's autograph tempo markings in 420 lists of pieces of similar character. Thus, a comparison of slower and quicker movements is made possible by 434 music examples, and there follows a wide-ranging collection of relevant texts taken from historical sources. The book does not claim to know "the single correct tempo" for the works of Wolfgang Amadeus Mozart. It hopes to be of assistance in the unavoidable search by every interpreter for the "true mouvement" of each work-for the work itself, for the performer, the instrument or instruments, the room, the public, the nature of the event. It follows that there can be no absolutely "authentic" tempo for Mozart's works. And yet his tempo markings, since he chose them so meticulously, should be taken equally seriously with the other parameters of his famously precise notation.
Description based on print version record.
KU Select 2019: HSS Backlist Books
Keywords: Music / Reference; Music; Electronic books